Policía comunitaria, reforma y confianza ciudadana. En el período 2007 - 2015 - Grijalva Córdova, Andrés Eduardo (2017)
The Community Police presents itself as a widely disseminated image of institutional police reform in the Latin American region. Reducing crime levels as well as increasing levels of public trust towards the institution is the central objective of this reform process. The present work focuses on analyzing the institutional reform process of the National Police of Ecuador, having as a presentation card, the Community Police and how the application of this police model has contributed to improve citizen confidence towards all police institution by means of significant changes in the levels of institutional management and changes in police education models that lead to the realization of a true police community spirit.